Exploring Digital Literacy Among Junior High School Students in Marginalized Areas: A Qualitative Case Study in Lembang District - Nawir, Rezki Adilah; Mukhlisin, Mukhlisin; Nur, Hasanah; Ashadi, Ninik Rahayu (International journal of technology and education research, 2025)
This study aims to describe the digital literacy levels of Phase D students (Grades VIII and IX) in three junior high schools classified as severely underdeveloped in Lembang District, Pinrang Regency, South Sulawesi. Employing a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The results indicate that most students have acquired basic digital skills, such as operating computers, using word and data processing software, and understanding the use of the internet and email. However, awareness of digital security remains very low. Major challenges include limited infrastructure, such as the small number of available computer devices, unstable electricity, and restricted internet access. Despite these constraints, students demonstrate strong enthusiasm, and teachers show initiative in maximizing available resources to support digital learning. This study recommends improving infrastructure, providing continuous teacher training, and implementing contextual learning strategies to strengthen digital literacy development in 3T (frontier, outermost, and disadvantaged) regions.